Evidence of Haplorchis taichui infection as pathogenic parasite: Three case reports - Sukontason K. (2014)
Haplorchis taichui is the minute intestinal fluke which parasitizes the small intestine of humans and other mammals. We present the pathology in the small intestine of 3 human cases caused by H. taichui. Microscopic examination revealed mucosal ulceration, mucosal and submucosal haemorrhages, fusion and shortening villi, chronic inflammation, and fibrosis of the submucosa. This finding clearly indicated H. taichui as pathogenic; thus prevention of infection and treatment should be paramount. © 2005 Taylor & Francis.